The effect of pilates reformer-based exercises compared to pilates mat-based exercises on general lower back pain and function in individuals suffering from non-specific lower back pain - Ferreira, Natalia Francisca (Department of Human Biology, 2025)
Background: Chronic non-specific lower back pain is a debilitating musculoskeletal ailment affecting approximately 85% of adults worldwide who will, at some point in their lifetime, experience lower back pain. Approximately 40% of individuals with acute lower back pain progress into a state of chronic pain over time (Lim, Poh, Low, & Wong, 2011). Pilates has been increasingly utilised in the treatment of individuals with lower back pain. Although previously characterised as an intensive and rigorous exercise modality, Pilates has, over the years, been modified to allow diverse age groups to use it as a rehabilitative tool. Aims: The study aims to compare Pilates Reformer-based exercises to Pilates mat-based exercises in its effectiveness in alleviating pain and movement disability in individuals afflicted with chronic non-specific lower back pain. Methods: Twenty-nine participants with chronic non-specific lower back pain, aged between 25 and 60 years old, were randomly assigned to one of the six-week interventions, being either reformer-based or mat-based. During the first consultation, the following assessments were completed: anthropometry measurements, flexibility, mobility, stability, pain, and disability ratings. Following the six-week interventions, all measurements will be repeated. Results: At baseline testing, both the Pilates mat-based group (50%) and the Pilates reformer-based group (53.3%) showed similar outcomes when assessing disability based on their Roland-Morris Disability Questionnaire (RMDQ) scores however, there was no statistically significant difference. (p = 0.858). 85.7% of the Pilates mat-based group hada high NPRS score at baseline compared to 66.7% of the Pilates reformer-based group. A Fishers exact test was conducted to determine the differences in proportions between the two groups, p = 0.858. There was a greater distribution of individuals with good stability in the Pilates reformer-based group (66.7%) compared to the Pilates mat-based group (28.6%) at baseline. This result was based on their performance in the Trendelenburg test and the bridge with leg extension test (BwLE), (p = 0.04). The statistical analysis revealed no significant associations between pain and disability ratings. (p > 0.05) However, there was a moderately strong significant association between the intervention group stability. (φ = 0.381, p = 0.04) Repeated measures ANOVA showed no significant changes over time (p = 0.088) or a group x time interaction (p = 0.487) for mobility that was measured using the Sit-and-Reach outcome variable. However, the Pilates reformer-based group showed a significant improvement in mobility, as measured by the active Straight-leg-raise test (ASLR) (p = 0.033), compared to the Pilates mat-based group, which did not show significant improvement in ASLR outcomes (p = 0.111). No group x time interaction was present for the changes in ASLR between the two groups. No significant changes were found in the BwLE or Trendelenburg in any of the two groups that was statistically analysed using McNemar Tests. Conclusion: No intervention modality could show a significantly greater improvement in mobility and stability outcomes compared to the other modality following a six-week Pilates intervention to manage non-specific lower back pain. However, Pilates reformer-based intervention showed to be an effective therapeutic rehabilitation tool for individuals suffering with chronic non- specific lower back pain and the management thereof insofar as disability, stability, mobility, and pain is concerned. The results may assist clinicians in decision-making regarding the treatment of individuals who suffer with chronic non-specific lower back pain.